The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.30802/aalas-jaalas-17-000128
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Aqueous and Alcohol-based Agents for Presurgical Skin Preparation Methods in Mice

Abstract: Preparing the skin of rodents for surgery often involves multiple applications of antiseptic agents. However, fewer applications may achieve the same antiseptic outcome. We evaluated the antimicrobial efficacy and effects on intraoperative body temperature of various surgical scrub agents, including novel waterless alcohol-based (WAB) options. Prior to ventral laparotomy, female C57BL/6 mice were treated with 0.9% saline (control); 70% ethanol; 10% povidone-iodine alternated with saline or 70% ethanol; 2% chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…In one study comparing various aqueous and alcohol-based agents for aseptic preparation of mice prior to a 15 min surgery, it was found that use of a 70% isopropyl alcohol rinse resulted in a more rapid decrease in body temperature than other rinses, including chlorhexidine solution. 14 However, all mice ended up at a similar temperature by the conclusion of the surgery. Unlike this study, no surgical drapes were used.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In one study comparing various aqueous and alcohol-based agents for aseptic preparation of mice prior to a 15 min surgery, it was found that use of a 70% isopropyl alcohol rinse resulted in a more rapid decrease in body temperature than other rinses, including chlorhexidine solution. 14 However, all mice ended up at a similar temperature by the conclusion of the surgery. Unlike this study, no surgical drapes were used.…”
Section: Discussionmentioning
confidence: 97%
“…1013 In the clinical experience of one author (RK) some high-quality, high-volume spay–neuter (HQHVSN) clinicians use a chlorhexidine rinse instead of alcohol in an effort to reduce the risk of perioperative hypothermia, particularly in their pediatric patients. However, the effect of alcohol rinses on mice is nuanced, with a rapid decrease in temperature followed by a rebound effect, 14,15 and it is unclear whether the use of an alcohol rinse would affect cats similarly to mice.…”
Section: Introductionmentioning
confidence: 99%
“…4,7,34 Although these methods are generally accepted as best current practice, the effectiveness of presurgical skin preparation methods in rodents and their effects on surgical wound healing has recently prompted investigation. 11 The goal of the present study was to evaluate 4 skin preparation methods for their ability to achieve antisepsis and to assess their effects on incisional wound healing. The data reported herein indicate that all methods were equally effective in achieving asepsis and resulted in satisfactory wound healing by day 7 after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…39 Triplicate application using alternating antiseptic scrub or solution and rinse has been the long-time standard in the veterinary field for preoperative skin preparation and is also the standard requirement for rodent surgery. 3,7,15,26 A recent evaluation of triplicate application of skin antiseptic preparation agents found that skin preparation can be achieved with 1 or 2 applications of antiseptic preparation. 7 Another study indicated that a different waterless alcohol-based agent was effective for antiseptic preparation after a single application in dogs.…”
mentioning
confidence: 99%
“…3,7,15,26 A recent evaluation of triplicate application of skin antiseptic preparation agents found that skin preparation can be achieved with 1 or 2 applications of antiseptic preparation. 7 Another study indicated that a different waterless alcohol-based agent was effective for antiseptic preparation after a single application in dogs. 20 This current study further explores alternative antiseptic skin preparation agents for mice that are used in the medical profession.…”
mentioning
confidence: 99%